Gene expression of the gonadotropin receptors and anti-Müllerian hormone in early maturing male Atlantic salmon parr, Salmo salar - Trombley, Susanne (Karlstads universitet, 2009)
An up-regulation of gene expression of the gonadotropin receptors FSHR and LHR, and a down-regulation of anti-Müllerian hormone (AMH), in the gonads of early maturing male Atlantic salmon parr (Salmo salar) have been shown to take place during the process of sexual maturation. It has however not been determined if this happens prior to or after the onset of spermatogenesis. The aim of this study was to see if such an up-regulation of the gene expression of FSHR and LHR mRNA, and down-regulation of AMH in the gonad tissue could be seen prior to the onset of spermatogenesis in early maturing salmon. For this study gonad tissues were sampled before and after the onset of spermatogenesis. Small pieces of testis tissue were removed using surgery from individually tagged one year old male Atlantic salmon parr in April prior to the onset of spermatogenesis. The same salmon were sampled again in July and maturing and non-maturing fish could be distinguished by differences in GSI. Each tissue sample from April could be matched with the July sample from the same individual by pit-tag numbers. This made it possible to separate the April samples into a maturing and non-maturing group. Gene expression levels were analysed using real-time PCR. The findings of this study showed that all three genes were expressed in the gonads in April but no significant difference in expression levels between maturing and non-maturing salmon was seen for any of the genes, which indicate that no up- or down-regulations had taken place in early maturing fish at this time. In July however, total FSHR and LHR expression levels/testis were significantly higher in maturing salmon which is in accordance with previous studies. AMH expression levels/unit RNA in July were found to be on average 25 times higher in the non-maturing group. A 100-fold drop in AMH from April through July was seen in the maturing fish, while only a 4-fold drop was seen in the non-maturing group which may indicate that a down-regulation of AMH expression took place as ...